Generalization relation in UML model elements - Pons, Claudia Fabiana (^p Datos electrónicos (1 archivo : 33 KB))
In this paper we analyze the concept of Generalization in the UML metamodel. We revise the kinds of generalization/specialization relations between UML model elements that can be expressed. We arrive to the conclusion that the Generalization relationship provided by the UML actually embraces two different generalization/specialization relations: an incremental relation and an overriding relation. Nature of each relation is very different, and it must be clearly distinguished in the UML in order to avoid wrong interpretation of UML models.